PEMBACAAN POSISI KOORDINAT DENGAN GPS SEBAGAI PENGENDALI PALANG PINTU REL KERETA API SECARA OTOMATIS UNTUK PENAMBAHAN APLIKASI MODUL PRAKTIK MIKROKONTROLER - Herlambang Sigit Pramono (Faculty of Engineering, Universitas Negeri Yogyakarta, 2011)
ABSTRACTThe purpose of this research is to add GPS application on practicum module of microcontroller for autoimatic railway barrier application. The method of this research is experimental design by designing the equipment of railway barrier based on GPS coordinates to develop modul application of microcontroller practicum. Data were collected from observation and measurement; the function from each part of the tool was observed while the latitude and longitude coordinates of the point in some locations were measured by the made tool. The data were analyzed by descriptive analysis for the function of each part of the tool and the measurement of coordinates were analyzed its erorr. The findings of the research showed that GPS could give the information about the position for both latitude and longitude coordinates if the accepted satelite signal met the standard requirement. Then, compared with the tools in market, the result from the made tool had error level of 0.82’ for latitude coordinate and 101,4’ for longitude coordinates.Keywords: GPS, microcontroller